Low-Molecular Weight Cow Colostrum Components in Functional Nutrition - Bozhkov, A.I.; Ivanov, E.G.; A.Y. Al Begai, Mohammad; M.A. Alsardia, Mohammad; Kurguzova, N.I. (Journal of Nutritional Therapeutics, 2017)
Background: The concept of functional nutrition has been actively developed in recent years. LMWCC contains biologically active compounds of natural origin and can be promising components of functional nutrition. Methods: Wistar rats (intact, rats with Cu-induced toxicosis and rats with Cu-induced toxicosis, who received LMWCC per os in different doses of 0.01, 0.05, 0.1, 1, 2, 3 mg / 100 g of body weight of the animal). The effect of low-molecular weight components of cow colostrum (LMWCC) have been studied on the some physiological and biochemical parameters (body weight, temperature, ability to perform work, activity of aspartate aminotransferase, alanine aminotransferase, cholesterol, triacylglycerides, creatinine, albumin, gamma-glutamyltransferase and lipid hydroperoxides) in experimental animals with Cu -induced toxicosis. Results: It was found that LMWCC in small doses (0.05-0.1 mg / 100 g of weight) restored the growth rate, body temperature and partially working capacity in the test "swimming with a load" of animals with Cu-induced toxicosis. Restoration of physiological parameters in animals with Cu-induced toxemia correlated with activation of the antioxidant enzyme glutathione peroxidase and a decrease in serum hydroperoxides in blood serum. It was suggested that LMWCC can be promising components of functional nutrition for various toxicoses. Conclusions: LMWCC has antioxidant properties in relatively small doses (0.05-0.1 mg / 100 g of weight). Restoration of the physiological characteristics of animals with Cu-induced toxicosis correlates with the elimination of oxidative stress. Large doses of 1 mg / 100 g of body weight and more manifest pro-oxidant properties